Effect of different grazing systems on the pasture flora - Rosito, Jumaida M.; Maraschin, Gerzy E. (Pesquisa Agropecuaria Brasileira, 2014)
A pasture of Paspalum guenoarum Arech. and Desmodium intortum (Mill.) Urb. established in 1978 at the Estação Experimental Agronômica - UFRS, Guaíba, RS, was evaluated by phytosociological surveys in the summer of 1980 and fall and spring of 1981. The evaluation aimed to know the pasture behaviour when submitted to different grazing systems with cattle. The alterations in the species frequency were evaluated along a transect line using only one pin. High grazing pressures increased the Cynodon dactylon (L.) Pers. and Paspalum notatum Flueg. frequencies (P<0.05) while the frequency of litter increases at the lower grazing pressures (P<0.05). Medium and long rest periods were favorable (P <0.05) to Paspalum guenoarum Arech. and Piptochaetium montevidense (Spr.) Parodi. The frequency of the other pasture species were not affected by the grazing systems employed (P>0.05).